Drawing the line in use of instant messaging - Leow, Serena Wai Yee *; Chee, Kwan Foong *; Long, Chiau Ming * (Star Media Group Berhad, 2023)
USING mobile instant messaging applications (MIM) such as WhatsApp and WeChat has become an integral part of our everyday communication.